(untitled) - Milne, George W. A. (Aldershot, England, 2000)
Providing records for all the major drugs currently used in endocrinology, Milne, long a researcher at the National Institutes of Health, presents monographs for 818 endocrine agents and steroids. For each, he identifies the chemical name and a list of trade names and synonyms; the Chemical Abstracts Service Registry Number; the European Inventory of Existing Commercial Chemical Substances Number; and the Merck Index Number from the 12th edition. He describes the physical properties of each compound, known biological activity, indicated applications, structure, any acute toxicity data, and the manufacturers and suppliers. They are listed by function and indexed by name and synonym and numbers.
Keywords: Endocrine glands,Steroid drugs,Hormone therapy,Thuốc Steroid,Hoóc môn liệu pháp,Tuyến nội tiết; Effect of drugs on,Ảnh hưởng của thuốc